2017
DOI: 10.1016/j.polymer.2017.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Tuning nanophase separation behavior in segmented polyhydroxyurethane via judicious choice of soft segment

Abstract: based soft segments, with divinyl benzene dicyclocarbonate and Dytek-A as hard segment and chain extender, respectively. These NIPU polymers were characterized by small-angle X-ray scattering (SAXS), atomic force microscopy (AFM), dynamic mechanical analysis (DMA), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR) and tensile testing. SAXS reveals that the NIPUs with 30-40 wt% hard segment are nanophase separated with interdomain spacings of 9-16 nm. DMA reveals that PTMO-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 110 publications
5
55
0
Order By: Relevance
“…Most previous PHU studies have focused on the synthesis of cyclic carbonate monomers and their subsequent polymerization into single‐phase thermoplastics or crosslinked thermosets, or on catalysis of the cyclic carbonate aminolysis reaction . Few studies have investigated segmented, nanophase‐separated PHU and established an understanding of their structure–property relationships . Leitsch et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous PHU studies have focused on the synthesis of cyclic carbonate monomers and their subsequent polymerization into single‐phase thermoplastics or crosslinked thermosets, or on catalysis of the cyclic carbonate aminolysis reaction . Few studies have investigated segmented, nanophase‐separated PHU and established an understanding of their structure–property relationships . Leitsch et al .…”
Section: Introductionmentioning
confidence: 99%
“…Beniah et al . have also demonstrated that nanophase separation in PHUs can be significantly tuned via judicious choice of soft segment . Despite these advances, segmented PHUs exhibit generally inferior thermal and mechanical properties relative to isocyanate‐based, segmented PU .…”
Section: Introductionmentioning
confidence: 99%
“…The DMA results for PHU‐Ac reflect the characteristic of single‐phase polymeric material and show that hydroxyl group functionalization with an acetyl group results in loss of nanophase separation despite the absence of hydroxyl groups which participate significantly in intersegmental hydrogen bonding in PTMO‐based PHU . Thus, although elimination of intersegmental hydrogen bonding in PHU by using polybutadiene‐based soft segment leads to excellent nanophase separation with narrow interphase, the elimination of hydroxyl groups necessary for such intersegmental hydrogen bonding in PTMO‐based PHU by functionalization with acetic anhydride results in the loss of nanophase separation itself.…”
Section: Resultsmentioning
confidence: 84%
“…The nanophase separation in PTMO‐based PHU is accompanied with broad interphase, which is due to a significant level of intersegmental hydrogen bonding between the hydroxyl groups to the soft segment . When a soft segment with no potential for intersegmental hydrogen bonding is used, such as polybutadiene‐based soft segment, nanophase‐separated PHUs with a much sharper domain interphase like that exhibited by conventional thermoplastic PU elastomer are obtained . Recently, Torkelson et al also reported that incorporating amide‐based, diamine diamide chain extender results in significant improvement in nanophase separation and properties of PHUs .…”
Section: Introductionmentioning
confidence: 99%
“…[13] Glass transition temperatures and mechanical properties such as hardness and flexibility can be tailored by incorporation of soft and hard segments and through careful selection of polyols. [14,15] These segments also affect amounts of crystalline and amorphous structures developed and provide both abrasion and solvent resistance.…”
Section: Polyurethanesmentioning
confidence: 99%